Genetic mapping of endogenous RD-114 retroviral sequences of domestic cats. - Reeves, R H (1985)
The RD-114 family of endogenous retroviral sequences in domestic cats has been shown to consist of approximately 20 copies of genetically divergent virogenes per haploid genome. The chromosomal localization for four endogenous sequences (RDV1-4) was accomplished by correlating the occurrence of specific feline chromosomes with diagnostic viral DNA fragments in a panel of cat X rodent somatic cell hybrids. Analysis of the hybrid panel revealed that endogenous RD-114 sequences are dispersed on multiple cat chromosomes, that certain proviral segments are polymorphic with respect to the presence or absence of virus, and that a restriction fragment characteristic of inducible RD-114 resides on a single feline chromosome (B3), probably at a single locus.